ANALISIS SOSIOLOGI SASTRA DALAM CERPEN “MAUTHINI” KARYA AMANI ISMAIL BERDASARKAN PERSPEKTIF ALAN SWINGEWOOD - Dzun Nur Nafi'ah Muamaroh; Alya Afifah Maliyanah; Laily Fitriani (Afshaha: Jurnal Bahasa dan Sastra Arab, 2022)
Literary works have a relationship with social conditions. such as in Mauthini's short story which discusses the state of the Palestinian people who are under attack by Israel. The purpose of this article: 1) To describe the portrait of the suffering experienced by the Palestinian people (2) To describe the portrait of the sacrifices of the Palestinian people during the uprising. This type of research is qualitative, descriptive, and literature. Data collection uses reading and note-taking techniques. The technical analysis of this research data is data reduction, data exposure and conclusion drawing. The results of this study have found a portrait of the suffering and sacrifice of the Palestinian people that shows the concept of the sociology of literature by Alan Swingewood. In the portrait of the suffering of the Palestinian population, there are 5 quotes that contain elements of suffering: (1) Wounded with blood. (2) Scream in heart (3) Victims fall. (4) Destruction of housing (5) Children victims of Israeli attacks. (6) Oppressed Palestine. In the portrait of the sacrifice of the Palestinian population kesimpulan, there are 3 quotes about the suffering of the Palestinian population: (1) Sacrificing their faith. (2) Muhammad's courage to the last drop of blood. (3) Sacrifice with Muhammad's martyrdom in the short story "Mauthini" by Amani Ismail. Keywords: Short Story, Palestine, Suffering, Sacrifice